Meta-analysis on the Diagnostic Performance of p16/Ki-67 Dual Immunostaining for Cervical Cancer Screening - Okoturo, Eyituoyo; Rabiu, Kabiru (Asian Pacific Journal of Cancer Biology, 2023)
Background: This article discusses cervical cancer and its higher incidence in LMIC compared to HIC due to limited resources and poor prevention strategies. It is preventable through early detection of persistent high-risk HPV infection, which is a critical promoter. Screening methods have evolved from pap smear cytology to HPV-DNA testing and currently to co-testing, but these methods still result in false positives and high colposcopy referrals. p16/Ki-67 dual immunostaining was proposed as a biomarker for cervical cancer triage due to its ability to detect HPV-mediated neoplastic transformation. The aim of the study was to evaluate the sensitivity and specificity of this dual staining method through a review and meta-analysis of published data. Material and Methods: The search was based on PRISMA guidelines using specific MeSH terms and keywords. The search was limited to publications that compared p16/Ki-67 dual immunostaining to Pap cytology and/or high-risk HPV-DNA and included colposcopy biopsy results as the diagnostic standard. The study focused on diagnostic performance outcomes such as sensitivity, specificity, and diagnostic odds ratio. To be eligible for meta-analysis, a publication must report the diagnostic performance at predicting CIN2+. Results: A total of 24 studies were included in the review and 21,450 samples were used for dual immunostaining. The results showed that dual immunostaining was significantly more sensitive than pap cytology (75.9% compared to 71.1%) and had a higher specificity (79.7% compared to 64.3% for pap cytology and 48.9% for HPV-DNA). A meta-analysis showed that dual immunostaining had a higher pooled diagnostic odds-ratio compared to pap cytology and HPV-DNA, indicating a better test power. Conclusions: The study suggested that dual immunostaining is a better approach for detecting HPV-induced cervical cancer compared to traditional screening methods. The authors suggest that despite its reduced sensitivity, dual immunostaining should be considered as a promising alternative, especially in large-scale testing.